CHALLENGES IN MANAGING NEGLECTED MALIGNANT BONE TUMORS, EXPLORING THE CAUSES AND THERAPEUTIC HURDLES AT A TERTIARY CARE INSTITUTE IN A LOW –MIDDLE INCOME COUNTRY - Farman Ullah; Shafi Ul Haq; Sohail Rehman; Fareeha Khalid; Waqas Ahmad; Muhammad ishfaq; Baqir Hussain (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Background: Orthopedic oncology commonly affect bones, soft tissue, and musculoskeletal system are generally neglected and have devastating effects on physical and emotional health if not treated. It is needed to explore therapeutic challenges associated with neglected orthopedic oncology.Material and Method: A descriptive cross-sectional study was conducted at Hayatabad Medical Complex and Rehman Medical Institute, Peshawar from May 2016 to June 2021. Tumors were categorized as neglected if there was a delay of over three months in seeking treatment. Tumor staging included X-rays, chest radiographs, full blood workups, MRI of the affected limb, and chest CT scans, using the Enneking staging approach. Data on age, gender, tumor site, histology, educational and socioeconomic status, prior treatments, and reasons for delay were collected and analyzed with SPSS- 22.Results: Of 470 orthopedic oncology cases, 116 (24.6%) were neglected malignant bone and soft tissue tumors. These included osteosarcoma (62.5%), Ewing sarcoma (25%), and chondrosarcoma (12.9%). Delays in treatment averaged 9.4 months, mainly due to financial constraints (88%), lack of awareness (90%), and limited healthcare facilities (27%). Traditional bone setters were consulted in 68% of cases, with 10% misdiagnosed by surgeons. Most cases were advanced (stage III or II-B) and treated with amputation, chemotherapy, or radiation.Conclusion: Study found a high proportion 24.6% cases as neglected malignant bone and soft tissue tumors. The majority were osteosarcomas 62.5%, followed by Ewing sarcomas 25% and chondrosarcomas 12.9%. Delays in seeking treatment averaged 9.4 months, primarily due to financial constraints, lack of awareness, and limited healthcare facilities.